A comparison of ER-2 measurements of stratospheric water vapor between the 1987 Antarctic and 1989 Arctic Airborne missions - Kelly, K. K.; Tuck, A. F.; Heidt, L. E.; Loewenstein, M.; Podolske, J. R.; Strahan, S. E.; Vedder, J. F. (1990)
Vertical profiles of water vapor inside the Antarctic vortex have been compared with those taken outside it over Punta Arenas (53 deg S, 71 deg W). A similar exercise was performed with Arctic vortex profiles and those taken over Stavanger (59 deg N, 6 deg E). Residual water, defined as the stratospheric water vapor mixing ratio with the contribution from methane oxidation subtracted, is also shown as profiles inside and outside the vortex for both missions. The Arctic and Antarctic profiles of water vapor and residual water are compared. Locally dehydrated air was evident both inside and outside the Antarctic vortex, but such dehydration was not evident in and around the Arctic vortex. Arctic profiles of residual water are consistent with nontropical entry for some air.